2014
DOI: 10.1016/j.bbrc.2014.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of structural stability and ligand binding after removal of the conserved disulfide bond in tear lipocalin

Abstract: Disulfide bonds play diverse structural and functional roles in proteins. In tear lipocalin (TL), the conserved sole disulfide bond regulates stability and ligand binding. Probing protein structure often involves thiol selective labeling for which removal of the disulfide bonds may be necessary. Loss of the disulfide bond may destabilize the protein so strategies to retain the native state are needed. Several approaches were tested to regain the native conformational state in the disulfide-less protein. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In a comparison of wild-type protein and single point mutation (I188K), it has been observed that disulfide bond mutation in I188K/S19C/G24C had a better stability and the activity of protein remained longer (Fig. 3), indicating that the disulfide bond played an important role in the stability of protein [10, 18, 22, 30]. I188K/S19C/G24C was more stable than A138E/R50C/Q147C and S190Y/E183C/I188C at 4 °C, 25 °C and 37 °C (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of wild-type protein and single point mutation (I188K), it has been observed that disulfide bond mutation in I188K/S19C/G24C had a better stability and the activity of protein remained longer (Fig. 3), indicating that the disulfide bond played an important role in the stability of protein [10, 18, 22, 30]. I188K/S19C/G24C was more stable than A138E/R50C/Q147C and S190Y/E183C/I188C at 4 °C, 25 °C and 37 °C (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of intrinsic cysteine residues in some proteins complicates site-selective conjugation if those residues are not the ideal conjugation target. Moreover, intrinsic cysteine residues are usually present in disulfide bonds, sustaining the protein’s conformational stability [ 9 , 10 ]. Therefore, labeling a fluorophore or other hydrophobic moiety at these positions might compromise overall protein stability, and conjugation with a small molecule can significantly decrease the enzymatic activity [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%